(untitled) - Dupuy, Trevor Nevitt (London, 1965)
Here is the story of those fearless and selfless bands of men who fought behind the lines to free their countries from the Japanese invaders in south-east Asia and from their own Fascist and Nazi rulers in Europe.
Keywords: World war, 1939-1945; Asia